(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In Iraq, the number of mobile phone users has increased dramatically During the past 15 years. Mobile network technologies are rapidly expanding worldwide, increasing the number of smart devices and mobile base stations. Placing mobile base stations in heavily populated areas, such as close hospitals and government departments, has triggered severe fear about potential health risks. The Iraqi Ministry of Environment released guidance for measuring magnetic waves emission by base stations used in mobile networks